1987
DOI: 10.1098/rstb.1987.0040
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the planktonic ecosystem of the North Sea in the context of oil and gas development

Abstract: Planktonic organisms are the primary source of food for the top level of the marine food chain, the fish. Yet only part of the plankton is ingested by fish, the remainder sediments to the bottom to provide food for benthic organisms (which may in turn be grazed by demersal fish) and to contribute to a detrital sink. Although the relative proportions of the plankton entering each of these compartments is still a matter of debate, some indication of its importance as a resource can be gauged from the North Sea f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Monthly sampling of plankton in the North Sea since 1948 has indicated a substantial decline in zooplankton, but the decline is more likely to have been caused by changes in fish grazing pressure than the activities of the petroleum industry (Ref. 42). Studies of the Exxon Valdez spill demonstrated the potential for low concentrations of hydrocarbons to affect the growth of juvenile salmon (eg Ref.…”
Section: Rocky Shoresmentioning
confidence: 99%
“…Monthly sampling of plankton in the North Sea since 1948 has indicated a substantial decline in zooplankton, but the decline is more likely to have been caused by changes in fish grazing pressure than the activities of the petroleum industry (Ref. 42). Studies of the Exxon Valdez spill demonstrated the potential for low concentrations of hydrocarbons to affect the growth of juvenile salmon (eg Ref.…”
Section: Rocky Shoresmentioning
confidence: 99%